High rate of microbleed formation following primary intracerebral hemorrhage. Issue 8 (26th August 2015) - Mackey, Jason; Wing, Jeffrey J.; Norato, Gina; Sobotka, Ian; Menon, Ravi S.; Burgess, Richard E.; Gibbons, M. Chris; Shara, Nawar M.; Fernandez, Stephen; Jayam‐Trouth, Annapurni; Russell, Laura; Edwards, Dorothy F.; et al.
Abstract : Background: We sought to investigate the frequency of microbleed development following intracerebral hemorrhage in a predominantly African‐American population and to identify predictors of new microbleed formation. Aims and/or hypothesis: To investigate the frequency and predictors of new microbleeds following intracerebral hemorrhage. Methods: The DECIPHER study was a prospective, longitudinal, magnetic resonance‐based cohort study designed to evaluate racial/ethnic differences in risk factors for microbleeds and to evaluate the prognostic impact of microbleeds in this intracerebral hemorrhage population. We evaluated new microbleed formation in two time periods: from baseline to 30 days and from 30 days to year 1. Results: Of 200 subjects enrolled in DECIPHER, 84 had magnetic resonance imaging at all required time points to meet criteria for this analysis. In the baseline to day 30 analysis, 11 (13·1%) had new microbleeds, compared with 25 (29·8%) in the day 30 to year 1 analysis. Logistic regression analysis demonstrated that baseline number of microbleeds [odds ratio 1·05 (95% confidence interval 1·01, 1·08), P  = 0·01] was associated with new microbleed formation at 30 days. A logistic regression model predicting new microbleed at one‐year included baseline number of microbleeds [odds ratio 1·05 (1·00, 1·11), P  = 0·046], baseline age [odds ratio 1·05 (1·00, 1·10), P  = 0·04], and white matter disease score [odds ratio 1·18 (0·96, 1·45). P  = 0·115]. Overall, 28 of 84 (33·3%) intracerebral hemorrhage subjects formed new microbleeds at some point in the first year post‐intracerebral hemorrhage. Conclusions: We found that one‐third of intracerebral hemorrhage subjects in this cohort surviving one‐year developed new microbleeds, which suggests a dynamic and rapidly progressive vasculopathy. Future studies are needed to examine the impact of new microbleed formation on patient outcomes.